2020
DOI: 10.1002/jcph.1647
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetic Model of Dexmedetomidine in a Heterogeneous Group of Patients

Abstract: Dexmedetomidine is a hepatically eliminated drug with sedative, anxiolytic, sympatholytic, and analgesic properties that has been increasingly used for various indications in the form of a short or continuous intravenous infusion. This study aimed to propose a population pharmacokinetic (PK) model of dexmedetomidine in a heterogeneous group of intensive care unit patients, incorporating 29 covariates potentially linked with dexmedetomidine PK. Data were collected from 70 patients aged between 0.25 and 88 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…Following this we considered size and age maturation; these two covariates have been shown to be important factors in pediatric PK models with a large age range and in previous dexmedetomidine studies. 6,8,16,17,[37][38][39] For size, we employed an allometric weight model with fixed or estimated scaling parameters. For maturation, we considered an exponential age model, a sigmoid Hill maturation model, a bodyweight dependent exponent model, and an age-dependent exponent model.…”
Section: Population Pk Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…Following this we considered size and age maturation; these two covariates have been shown to be important factors in pediatric PK models with a large age range and in previous dexmedetomidine studies. 6,8,16,17,[37][38][39] For size, we employed an allometric weight model with fixed or estimated scaling parameters. For maturation, we considered an exponential age model, a sigmoid Hill maturation model, a bodyweight dependent exponent model, and an age-dependent exponent model.…”
Section: Population Pk Analysismentioning
confidence: 99%
“…Importantly, population PK models can identify covariates that affect each individual's PK profile, facilitating personalized dosing. Several population PK studies of dexmedetomidine in pediatric populations have been reported, [5][6][7][8][9][10][11][12][13][14][15][16][17] often using a small number of individuals and frequent sample collection [median sample size 29, range 18-199 for pediatric ICU populations]. 7,[9][10][11][12]14,15 Strategies to address small sample size include pooled pediatric analyses, 17 creating "universal" models for both children and adults, 6,8 and Bayesian analyses with informative priors; 16 however, even these models only include information from at most around 130 children.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations